Positive Solutions for Nonlinear q-Fractional Difference Eigenvalue Problem with Nonlocal Conditions - Wafa Shammakh; Maryam Al-Yami (Abstract and Applied Analysis)
The problem of positive solutions for nonlinear q-fractional difference eigenvalue problem with nonlocal boundary conditions is investigated. Based on the fixed point index theory in cones, sufficient existence of positive solutions conditions is derived for the problem.